The Use of New Technologies in the Study of Pregnancy Disorders: The OMICS Approach - Visentin, Silvia; Bongiorno, Maria Caterina; Calanducci, Maria; Loris Marin, Loris Marin; Cosmi, Erich (Journal of Cardiovascular Medicine and Cardiology, 2017)
The “omics” technologies represent a new model of approach in the study of human disease. Metabolomics is defined as the quantitative measurement of the dynamic metabolic response of living systems to genetic, physical, pathological or developmental factors. Proteomics analysis of biological samples has the potential to identify novel protein expression patterns and/or changes in protein expression patterns in different developmental or disease states. In this manuscript we present the omics technologies applicated in obstetrics. The management of different pregnancy diseases could be improved by knowing their metabolic background. In this review we focused our attention on omics application for intrauterine growth restriction (IUGR), preterm birth and preeclampsia. Omics in IUGR field could help to discover novel biomarkers for early diagnosis, the molecular link between nutrient deprivation in utero and the increase in risk of developing cardiovascular illness and metabolic syndrome in adults. It could identify one or more therapeutic targets that allow to minimize the organ damage. Recently, the use of metabolomics permitted to discover significant differences in 70 proteins within the trophoblastic cells of women with pre-eclampsia when compared with healthy control women. Recently were identified proteins in cervical–vaginal fluid that could be useful to predict preterm labor in asymptomatic women: thioredoxin and interleukin-1 receptor antagonist. In conclusion, this approach can lead to new hypothesis-based medicine and provide a ‘‘shortcut’’ to obtain new biological insight.